Application of Business Games in Training of Employees of Regional Executive Bodies and Local Self-Government Bodies - A. V. Klushin (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2021)
The author raises the issues of applying innovative approaches in the educational and methodological process of training personnel, whose competence includes the implementation of measures to prevention of terrorism. The article discusses the features of conducting practical exercises in the simulation games form, their part and positive experience in the provision of education organization, and advanced training of employees of the antiterrorism commission apparatus in the constituent entities of the Russian Federation, executive authorities, and local self-government bodies.